Continuity of thin layers of an organic semiconductor induced by the modification of the gate insulator. Issue 41 (4th October 2022) - Łuczak, Adam; Waliszewski, Witold; Jerczyński, Krzysztof; Wypych-Puszkarz, Aleksandra; Rogowski, Jacek; Pietrasik, Joanna; Kozanecki, Marcin; Ulański, Jacek; Matyjaszewski, Krzysztof
Abstract : The change in the crystallization process of an organic semiconductor layer in the presence of a small amount of TiO2 nanoparticles from the Volmer–Weber mode to the Stranski–Krastanov mode is reported and explained. Abstract : In this work the unusual improvement in the performance of organic field effect transistors was explored after adding a very small amount (below 1 wt%) of hybrid nanoparticles containing TiO2 to poly(methyl methacrylate) (PMMA) used as the gate dielectric. TiO2 nanoparticles were prepared using the well-defined poly(styrene- co -acrylonitrile)- b -poly(acrylic acid)-poly(divinylbenzene) star-shaped template. It was found that the presence of hybrid nanoparticles did not affect the surface energy of the dielectric layers, but their roughness increased; in particular, a significant increase of the maximum peak height was observed. The density of such spikes increased with the content of hybrid nanoparticles. These spikes acted as heterogeneous nucleation centers for the crystallizing semiconductor, which was confirmed by the correlation between the concentration of hybrid nanoparticles and the density of the nucleation centers. It was concluded that the semiconductor deposited on neat PMMA cannot easily nucleate because of poor interaction with PMMA (thus the density of nuclei is low), and crystal growth occurs more upward than laterally resulting in layer discontinuity and formation of separated, high domains. The protruding spikes on the hybrid dielectric layers facilitated heterogenous nucleation and the formation of crystalline domains of the semiconductor. As a result, even ultrathin layers of the semiconductor were continuous. The discovered effect has opened new possibilities for the production of ultrathin and continuous layers of molecular materials that can be used in many fields of science and technology.